LITERATURE REVIEW STUDY: ANALYSIS OF THE ROLE AND OPPORTUNITIES OF TECHNOPRENEURSHIP IN INDONESIA - Siti Putri Luthfiyyah; Ritha F. Dalimunthe (Cahaya Ilmu Bangsa, 2024)
Technopreneurship is utilized by business people in all fields. Fields that usually utilize technopreneurship include education, pharmacy, hotels, and so on. Technopreneurship is actually not a product, but a synthesis of the future of a person, organization, nation and world. Therefore, a directional strategy and selection process is needed the right decisions in critical and complex times. This requires the help of universities and professional development programs. This research uses a literature review method, A research through comprehensive research and interpretation of literature related to a particular topic, which includes identifying research questions by searching and analyzing relevant literature using a systematic approach to carry out simplified data analysis. The results of this research show that there is a strong and positive relationship between technopreneurship and company growth. Indonesia needs it continue to develop the spirit of technopreneurship to support the economy. There is a strong positive relationship between technopreneurship and the growth of entrepreneurship. Enhancement The number of technopreneurs will increase business growth as a direct impact of expertise and skills possessed by entrepreneurs.